2021
DOI: 10.1002/jcp.30613
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in follicular development and maintenance of primordial follicular pool in the ovary

Abstract: The reproductive life span of the organism mainly depends on follicular development that maintains the primordial follicle pool in the cohort of follicles within the ovary.The total count of primordial follicles decreases with age due to ovulation and follicular atresia. Follicular atresia, a process of ovarian follicles degradation, mainly occurs via apoptosis, but recent studies also favor autophagy existence. Autophagy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 84 publications
0
31
0
Order By: Relevance
“…PI3K/AKT/mTOR signaling pathway is a pivotal regulator of autophagy 114 , 115 . Li et al 116 revealed that BMMSC-exo could ameliorate the inflammation and apoptosis of AFc by inhibiting the expression of PI3K/AKT/mTOR signaling pathway.…”
Section: Exosome Derived From Stem Cellsmentioning
confidence: 99%
“…PI3K/AKT/mTOR signaling pathway is a pivotal regulator of autophagy 114 , 115 . Li et al 116 revealed that BMMSC-exo could ameliorate the inflammation and apoptosis of AFc by inhibiting the expression of PI3K/AKT/mTOR signaling pathway.…”
Section: Exosome Derived From Stem Cellsmentioning
confidence: 99%
“…However, increasing evidence suggests that apoptosis is not the exclusive mechanism and that autophagy represents an alternative non-apoptotic process that contributes to the efficient elimination of granulosa cells and oocytes (Cassel et al, 2017;Corriero et al, 2021;Morais et al, 2012Morais et al, , 2016Sales et al, 2019;Santos et al, 2008;Thomé et al, 2009). Recently, a review paper by Bhardwaj et al (2022) has reported the implication of autophagy marker genes also in the process of atresia in mammals and involving all cell types forming the follicle. Autophagy recycles nutrients from degraded cell organelles in the follicle, and hence could provide the energy that may be required for future oocyte and egg production in vertebrates (Bhardwaj et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a review paper by Bhardwaj et al (2022) has reported the implication of autophagy marker genes also in the process of atresia in mammals and involving all cell types forming the follicle. Autophagy recycles nutrients from degraded cell organelles in the follicle, and hence could provide the energy that may be required for future oocyte and egg production in vertebrates (Bhardwaj et al, 2022). Whereas in mammals, apoptosis in cells that form the ovarian follicles is considered the main cellular mechanism mediating early ovarian atresia (Hsueh et al, 1994;Matsuda et al, 2012;Tilly, 1996aTilly, , 1996bTiwari et al, 2015), in fish, apoptosis is accompanied by autophagy at least during the late stages of follicular atresia (Miranda et al, 1999;Morais et al, 2012); thus suggesting the existence of another novel pathway during follicular atresia (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…After birth, with the animal growth and development, the majority of follicles undergo atresia and degeneration ( 3 ). Post-puberty only a few follicles develop to mature, but the absolute number of follicles decreases with age ( 4 ). If female animal has ovarian disease, the limited resources cannot be used effectively, which causes significant losses to the breeding industry.…”
Section: Introductionmentioning
confidence: 99%